2013
DOI: 10.1371/journal.pone.0053865
|View full text |Cite
|
Sign up to set email alerts
|

Public Information Influences Sperm Transfer to Females in Sailfin Molly Males

Abstract: In animals, including humans, the social environment can serve as a public information network in which individuals can gather public information about the quality of potential mates by observing conspecifics during sexual interactions. The observing individual itself is also a part of this information network. When recognized by the observed conspecifics as an audience, his/her presence could influence the sexual interaction between those individuals, because the observer might be considered as a potential ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 129 publications
0
13
1
Order By: Relevance
“…My current results on male guppy courtship behaviour differ from those of a recent study by Nöbel and Witte (2013), who compared the courtship behaviour of male sailfin mollies in the presence or absence of a conspecific audience. They found that male mollies spent less time following a stimulus female, but did not alter the frequency of their courtship displays, when a male audience was present compared to when either no audience was present or when the audience was comprised of three sexually mature females.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…My current results on male guppy courtship behaviour differ from those of a recent study by Nöbel and Witte (2013), who compared the courtship behaviour of male sailfin mollies in the presence or absence of a conspecific audience. They found that male mollies spent less time following a stimulus female, but did not alter the frequency of their courtship displays, when a male audience was present compared to when either no audience was present or when the audience was comprised of three sexually mature females.…”
Section: Discussioncontrasting
confidence: 99%
“…the demonstrator) can provide benefits to the copier (e.g. reduced sampling costs), there can also be associated costs with copying for both the demonstrator and copier, such as increased resource competition and risk of sperm competition (Nöbel and Witte 2013;Dubois 2015;Castellano et al 2016). When demonstrators and eavesdroppers compete for the same limited resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated so-called 'audience effects' [43,44] during which males alter their mate choice behavior strategically in response to rival presence [45][46][47]. Poeciliid males, when faced with a rival male during their mate choice (which may observe and later copy their mating decisions) lower their sexual effort and conceal their mate preference, or they even trick their observers by interacting with the previously non-preferred female [32,[48][49][50][51][52][53][54].…”
Section: Copying Tendencies-part Of a Social Responsiveness Syndrome?mentioning
confidence: 99%